A benchmark testing technique to characterize the stress–strain relationship in materials based on the spalling test and a photomechanical method. (17th September 2019) - Forquin, Pascal; Lukić, Bratislav; Saletti, Dominique; Sallier, Laurent; Pierron, Fabrice
Abstract: The experimental testing of concrete and other brittle materials under high-strain rate tensile loading remains a major issue in many research fields and industrial applications. Among the experimental methods, the spalling technique provides a major advantage as it does not rely on a static mechanical balance of the sample. A short compressive pulse transmitted to the sample reflects from the rear free surface as a tensile pulse leading to sample tensile fracturing. However, the classic processing (i.e. Novikov's acoustic approximation) based on the measurement of the sample rear face velocity profile, relies on strong assumptions that can lead to an over-estimation of the material tensile strength. A new processing technique was proposed by Pierron and Forquin (2012 Strain 48 388–405) to derive the stress field and apparent Young's modulus using only data from an ultra-high speed camera. This purely inertial method is based on the time resolved measurement of axial displacement fields and the virtual fields methods (VFM). However, the measurement accuracy as well as uncertainty remains to be studied in more detail and better understood. In the present work, a series of spalling tests have been performed with a sample made of aluminium alloy behaving linearly elastic. Such test allows investigating a possible influence of several testing parameters (e.g. interframe time, lens focusing, number of pixels per period…), processing parameters (mainly the levels of spatial and temporal smoothing for regularization) as well as the influence of the camera sensor technology. The results are compared to data from strain gauges and to the expected Young's modulus and stress–strain response of the tested aluminium alloy, so the accuracy of measurements is evaluated. Finally, the spalling set-up applied to a sample of well-known mechanical properties appears to be a good benchmark to assess the quality of stress versus strain measurements based on photomechanical methods.